Perancangan dan Pengembangan Sistem Konseling Siswa di SMA Yos Sudarso - Leon, Jevin; Simanjuntak, Fredian (Journal of Information System and Technology (JOINT), 2024)
Yos Sudarso High School is the first Catholic private school and one of the oldest schools in Batam, Riau Islands, under the Tunas Karya Foundation. SMA Yos Sudarso still records the results of counseling guidance manually through handwriting in books. This process is considered ineffective and inefficient, especially when it comes to retracing the results of previous guidance. In addition, manual recording requires more time and energy to manage, organize, and update the content that has been created. Therefore, this research intends to design and develop a digital student counseling system that can facilitate counseling teachers in managing counseling guidance results. The method used for the development of student counseling system in this research is SDLC Waterfall model. The result of this research is a student counseling system that helps improve the operational efficiency of recording and managing student guidance results at Yos Sudarso High School.